2019
DOI: 10.1016/j.psyneuen.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Grief, depressive symptoms, and inflammation in the spousally bereaved

Abstract: Grief is conceptualized by strong negative emotions, which include longing, sadness, and preoccupations with thoughts, recollections, and images of the spouse. In the initial months after the loss of a spouse, those who are widowed are at risk for cardiovascular problems and premature mortality. In the general population, depression is characterized by chronic low-grade inflammation, a key predictor of cardiovascular problems, morbidity, and mortality. Although depression and grief share similarities, they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 48 publications
(55 reference statements)
1
38
0
2
Order By: Relevance
“…Some researchers have thus suggested that it is not interpersonal loss or bereavement but rather depression that is responsible for causing the increases in morbidity and mortality seen in bereaved individuals ( 9 , 12 , 49 , 89 , 98 ). On the other hand, though, research has shown that grief and depression are independently associated with health-damaging inflammation ( 99 ). Therefore, it may be the case that bereavement and depression are associated with similar but distinct patterns of inflammatory activity, and that interpersonal loss is a common precipitating stressful life event that may lead to both grief and depression.…”
Section: Psychobiology Of Bereavement From the Perspective Of Social mentioning
confidence: 99%
“…Some researchers have thus suggested that it is not interpersonal loss or bereavement but rather depression that is responsible for causing the increases in morbidity and mortality seen in bereaved individuals ( 9 , 12 , 49 , 89 , 98 ). On the other hand, though, research has shown that grief and depression are independently associated with health-damaging inflammation ( 99 ). Therefore, it may be the case that bereavement and depression are associated with similar but distinct patterns of inflammatory activity, and that interpersonal loss is a common precipitating stressful life event that may lead to both grief and depression.…”
Section: Psychobiology Of Bereavement From the Perspective Of Social mentioning
confidence: 99%
“…Specifically, widows and widowers showed enhanced proinflammatory cytokine production by in vitro lipopolysaccharide-stimulated peripheral blood leukocytes than did matched comparison subjects (Fagundes et al, 2018). When examining between-persons differences among widows and widowers, we found that individuals with higher grief severity had higher levels of proinflammatory T-cell-derived cytokines than those with less grief severity (Fagundes et al, 2019). We also examined the association between depressive symptoms and inflammation because we wanted to know whether the well-established relationship between elevated inflammation and greater depressive symptoms existed among widows and widowers (Kiecolt-Glaser, Derry, & Fagundes, 2015).…”
Section: Immune Activitymentioning
confidence: 99%
“…We found that those who experienced higher levels of depression exhibited elevated levels of T-cell-derived proinflammatory cytokines compared with those who had lower levels of depressive symptoms. However, depression did not explain the relationships with grief and proinflammatory cytokines (Fagundes et al, 2019).…”
Section: Immune Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Proinflammatory cytokines including interferon gamma, interleukin IL-6, and tumor necrosis factor alpha have also been shown to be associated with the level of an individual’s grief severity ( Fagundes et al, 2019 ). Takotsubo cardiomyopathy (ie, broken heart syndrome) is a vivid example of these interactions, where stress hormones cause abnormal movement of the heart muscle, resulting in typical angina symptoms and, in some cases, infarction.…”
mentioning
confidence: 99%